Glacial Lake Camelsfoot: a Late Wisconsinan advance stage proglacial lake in the Fraser River valley, Gang Ranch area, British Columbia - Huntley, David H.; Broster, Bruce E. (Canadian Journal of Earth Sciences, 1994)
In the Gang Ranch area, British Columbia, interaction between the regional physiography and ice flow during the Late Wisconsinan Fraser Glaciation resulted in the formation of a proglacial lake confined to valleys of the Fraser River and its tributaries. Lithostratigraphic and geomorphic evidence suggests that ponding was initiated in the Big Bar Creek area where the Fraser River is confined to a deep canyon in the Camelsfoot Range. During ice advance, a proglacial lake system developed that progressively deepened and reached a minimum upper elevation of approximately 710 m asl prior to being overridden by ice. We propose that this system be formally named "Glacial Lake Camelsfoot." A composite stratotype, comprising lithostratigraphic units associated with Glacial Lake Camelsfoot, is described from eight reference sections along Fraser River, Churn, and Lone Cabin creeks in the Gang Ranch area. Additional geomorphic evidence indicates that at the Fraser Glaciation maximum, the Cordilleran Ice Sheet in the study area ranged from 600 to 2000 m in thickness.